The voyage of the 'Fox' in the Arctic seas. A narrative of the discovery of the fate of Sir John Franklin and his companions. - M'Clintock, Francis Leopold, Sir, 1819-1907.; Godfrey, Wm. C. (William C.) (Philadelphia, J. T. Lloyd, 1860)
Mode of access: Internet.